Randomized Clinical Study of the Use of MTA and Biodentine™ for Pulpotomy in Primary Teeth - Lídia Regina da Costa Hidalgo; Luciano Aparecido de Almeida-Junior; Marília Pacífico Lucisano Politi; Paulo Nelson-Filho; Raquel Assed Bezerra Segato; Francisco Wanderley Garcia Paula-Silva; Léa Assed Bezerra da Silva (Association of Support to Oral Health Research (APESB), 2023)
Objective: To verify, through clinical and radiographic evaluations, the in vivo response of the dentin-pulpal complex of human primary teeth after pulpotomy with MTA and Biodentine™ in a follow-up period of 3, 6, and 12 months. Material and Methods: Thirty teeth were divided into MTA pulpotomy (n = 15) and Biodentine™ pulpotomy (n = 15) from children between 5 and 9 years of age, a randomized clinical trial with simple random sampling. The materials were inserted into the cavity after opening and removing the coronary pulp tissue. The cavity base consisted of glass ionomer cement and light-cured composite resin restoration. Clinical and radiographic analyses were performed after 3, 6, and 12 months. Statistical analysis by Fisher's exact test for dichotomous data at a 5% significance level was utilized. Results: Both materials caused color change after 12 months. However, MTA showed a higher percentage than Biodentine™ (p<0.0001). Pain was detected only with Biodentine™ at six months and mobility at 12 months (p=0.0013). Radiographically, after 12 months, periapical lesions, interradicular lesions, and internal resorption were evidenced in 13% of the cases for Biodentine™-treated teeth (p<0.0013). MTA induced pulp calcification in 13% of cases, unlike Biodentine™ (p<0.0013). Conclusion: BiodentineTM and MTA are suitable for clinical use in pulpotomy treatment, yet both materials lead to tooth discoloration.